Analisis Finansial Usahatani Padi Sawah (Oryza sativa L) Di Desa Kayu Elang Kecamatan Semidang Alas Kabupaten Seluma - Sarina; Edrianto; Indah Fitria (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2026)
Financial Analysis of Welshaw rice (Oryza sativa L) farming in Kayu Elang Village, Semidang Alas District, Seluma Regency. This study aims to examine the financial analysis of Welshaw rice farming in Kayu Elang Village, Semidang Alas District, Seluma Regency. The sample consists of financial farmers. The research was conducted from August 2025 to November 2025. The data used included both primary and secondary data. The variables analyzed were average production, production costs, revenue, income, and the R/C ratio. The results show that the average land area is 0.42 hectares. The average production is 931 kg of rice per farming unit, and the average production cost is Rp. 3,850,796 per unit, the average revenue is IDR 11,636,486 per unit, and the average income is Rp. 7,785,690 per unit, and the R/C ratio is 3.02. Thus, rice farming in Kayu Elang village is worth pursuing.